The Reliance of the Public of Baghdad on News Broadcasts on Satellite Channels as a Source of Information - Mohammad, Ammar Taher; Saeed, Shareef (ALBAHITH ALALAMI, 2019)
The importance of news broadcasts in society has increased after the domination of television over the mass media, especially after emerging the satellite channels, and spreading the satellite dishes among the public at large. As well as the great role played by the modern technology in the transmission of news and events happening at once. Such role has contributed, significantly, in changing the concept and values ​​of the news. The live broadcast of the events filmed is the news itself. In the midst of the great transformations and circumstances that Iraq went through after 2003, which witnessed political and security instability, and the large increase in the number of media, especially satellite channels, in Iraq and in the world. These factors have contributed to increasing the area of ​​influence of television in the lives of Iraqis through newsletters that made influence of television as a phenomenon that occupies the attention of the public for what produces of news and information on events and phenomena. The problem of the research is that there is some sort of ambiguity, weakness or lack of clarity in the reliance of the public in Baghdad on the news as sources of information. In light of the huge increase in the number of satellite channels at all levels (Iraq, Arab, and international), and in light of the fierce competition among those channels in presenting news services and news programs, especially news broadcasts, satellite channels endeavored to achieve a scoop as events, issues and crises following up; and to assure that those events, issues and crises will be seen, daily, by the viewers; and to increase the hours of broadcasting those services and programs, around the clock. All those factors contributed greatly to increasing the interest of the public in those news broadcasts in order to understand the meaning of events. Exposure to news has become one of the communication habits of the public, which they, often, practice daily. The public, moreover, may depend on the events, circumstances and crises experienced by the world around them in order to understand the environment that surrounds them. The research problem is summarized by the following question: To what extent can the public in Baghdad rely on the news broadcasts of satellite channels as a source of information? The importance of this study lies in the study’s attempt to monitor the reality of the Iraqi public’s reliance, especially the audience of the city of Baghdad, as it represents all spectrums of the Iraqi people, on news broadcasts provided by satellite channels in general. Exposing to the news broadcasts became of the of the public communication habits, and daily rituals practiced by individuals in order to achieve an understanding to what is happening around them about many events and issues covered. The significance of the study can be seen in creating an important and effective database, especially for the Iraqi researcher. As for the academic and research importance, the results of the research will be a starting point for the researchers in this regard, especially the research of the same concern; and the researches that follow in the field of media as a source of information. As the media library in Iraq lacks to such researches with some exceptions.